Accuracy of computer-assisted total knee arthroplasty related to extra-articular tibial deformities. (25th October 2013) - Tantavisut, Saran; Tanavalee, Aree; Ngarmukos, Srihatach; Yuktanandana, Pongsak; Wilairatana, Vajara; Wangroongsub, Yongsak
Abstract: Objective: To compare the accuracy of postoperative mechanical alignment in computer-assisted total knee arthroplasties (CAS-TKA) related to various degrees of extra-articular tibial deformity. Methods: We performed CAS-TKA on 30 knee models in which extra-articular proximal tibial deformities were preset to have malalignments ranging from 30° of varus to 30° of valgus. The knees were assigned to two groups, designated Group A (knees with ≤15° preoperative malalignment) and Group B (knees with >15° preoperative malalignment), and the postoperative mechanical alignment in the two groups was compared using a computer-assisted surgery (CAS) system. Resected bone pieces from the distal femurs and proximal tibias were measured with a digital Vernier caliper and the results compared with the CAS calculations to evaluate the execution accuracy of the bone resection. Results: There was no outlier in either group when a ±3° deviation from neutral mechanical alignment was set as the acceptance criterion. Interestingly, Group B showed significantly more outliers when the acceptance criterion was a deviation of ±2° (26.67%, p  = 0.0317) or ±1° (6.67%, p  = 0.0007) from neutral alignment. There was no statistical difference between the groups in terms of the execution accuracy of the bone resection. Discussion: The CAS-TKA approach provided significantly less alignment accuracy in tibia with greater preoperative frontal deformity, despite there being no outliers beyond ±3°.